A Survey on Introductory Statistics Classes in Japanese Medical Schools - Yamashita, Yoji; Sozu, Takashi; Tanioka, Kensuke; Omori, Takashi; Uesaka, Ayaka (Japanese Journal of Biometrics, 2015)
Few studies have investigated the content of introductory statistics classes for medical school students in Japan. Yet, to assure the quality of university statistics courses and develop a standard curriculum for them, it is necessary to assess the current condition of statistics education. Therefore, we collected data on the type of course (i.e., course title and targeted year for the students), field of specialty of the lecturer, course contents, and which textbooks were pre-specified for the lecture by analyzing the syllabi of statistics courses published on university websites. Next, the result of the survey is summarized. Of the 80 universities surveyed, 45 universities provided the online sylabi for the introductory statistics course. We identified 26 different course titles for statistics classes. Thirty courses (73.3%) were intended for first-year students. Eightteen courses (54.5%) provided two credits. The most common field of specialty for statistics lecturers was mathematics (43.2%). Further, we found that the course contents included various subjects related to mathematics. A total of 35 textbooks were specified. Finally, the conclusion is that mathematical concepts seem to be taught more often than statistical practice in introductory statistics classes. Further, there were large variations in each item of analysis except the target year.